The influence of the taphonomically active zone on peat formation: Establishing modern peat analogs to decipher mangrove sub-habitats from historical peats - Neely, Samuel H.; Raymond, Anne (Frontiers in Ecology and Evolution, 2023)
Mangroves create unique and highly productive wetland communities in intertidal zones of tropical and subtropical coastlines. Despite their many ecosystem services, such as carbon sequestration, mangroves remain threatened by climate change, sea-level rise, and human development. The inclusion of conservation paleobiology and long-term perspectives on how these ecosystems have responded to past environmental change can inform current policy and lead to more effective conservation and restoration management strategies for modern mangrove communities. In South Florida, humified plant debris, or peat, in mangroves provides this historical record. Our research takes a novel paleobiological approach by using plant organ- and taxon-based measures to describe the influence of the taphonomically active zone (TAZ: the zone near the surface of the substrate where taphonomic processes actively formation and degrade accumulated detritus) on the decomposition of mangrove peat with depth. This allows us to understand the taphonomic biases imposed on mangrove peat as it is sequestered into the sedimentological record and provides us with the paleoecological context to better interpret preserved peats and reconstruct past mangrove sub-habitats from peat cores. Accordingly, we collected modern surficial peat cores from two contrasting mangrove sub-habitats in Barnes Sound, FL. These surficial cores were characterized and compared to historical, deep cores from other South Florida mangrove peat deposits. By comparing the proportional abundance of mangrove peat constituents in these samples, we established modern analogs needed to interpret changes in the depositional environment of historical mangrove peats found in sediment cores, which is critical for understanding shoreline responses of mangroves to sea-level rise and anthropogenic change. We demonstrate that (1) leaf mat thickness may be a relative indicator of surficial peat decomposition rates because it correlates with the degree of tidal activity and detritivore access to the leaf litter layer; (2) root percentages are valid tools to differentiate between peats at depth, and can be used as relative indicators for the distance of in situ peat from shorelines; and (3) organismal signals, such as foraminifera and insect parts, provide a means for deciphering precursor mangrove sub-habitats from sequestered peats.